Ekosistem, Sosiosistem dan Geosistem Agribisnis di Dataran Tinggi Jawa Bara - Iwan Setiawan; Aris Sugianto (UNEJ e-Proceeding, 2018)
All this time, agribusiness in the highlands more observed of the potential aspect, whilethe threats are rarely considered. In fact, agribusiness in the highlands are vulnerable to theimpacts of environmental change, modernization and geological disasters. Based on humanecology perspective, this study aims to describe and illustrate the characteristics of the ecosystem,socialsystem and geosystem agribusiness in the highlands. The results showed that the ecosystemagribusiness in the highlands has undergone many changes, especially on components of climate,land, crops, livestock,water, plant pests and diseases. Transformation caused by the behavior ofsocial systems, both the pattern of efforts and the pattern of development, the less adaptive, notfriendly to the environment and not anticipatory against possible geological disasters. In fact, thehighlands of West Java, is located in a Bandung zone which dominated by volcanoes and traversedthe fault, so prone to volcanic eruptions, earthquakes, landslides and soil collapsed. Therefore,agribusiness development strategy in highlands must integrate ecosystems, social system andgeosystem. In order for the agribusiness actors more adaptive and anticipatory of geologicaldisasters, the disaster mitigation should be included in strategy. Moreover, the necessaryremodeling agribusiness approach, settlements and infrastructure engineering are more adaptiveand anticipatory in the highlands. So, need to strengthen social capital, especially network ofcooperation between communities, businessment, agricultural institutions, climatology agencies,geology agencies and ministries settlement and regional infrastructure.